2019
DOI: 10.4103/jehp.jehp_402_18
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the most appropriate variables for measuring the efficiency of Iranian public hospitals: Using Delphi technique

Abstract: CONTEXT: Selecting variables is a fundamental step in evaluating comparative efficiency because the results of measuring efficiency depend on the used variables. AIMS: The aim of this study is to provide a comprehensive set of input and output variables for measuring efficiency with an emphasis on application in general hospitals in Iran. MATERIALS AND METHODS: This study comprised a literature review followed by a Delphi survey process. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this study, the selection of input and output variables was guided by previous studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and the Delphi method [ 72 , 73 ]. The reason for using Delphi was to keep social distance during COVID-19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the selection of input and output variables was guided by previous studies [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and the Delphi method [ 72 , 73 ]. The reason for using Delphi was to keep social distance during COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…In the first round, all variables identified after review were submitted to the members of the Delphi team in the form of electronic files to determine the classification of variables (input variables, output variables, and undesirable variables). In the second round, a 5-point Likert scale questionnaire was used for scoring each variable based on its importance in the efficiency evaluation of tertiary hospital [ 72 ]. Each member of the Delphi panel rated variables on a scale of one (not important) to five (very important).…”
Section: Methodsmentioning
confidence: 99%
“…The literature show that efficiency is defined as the effectiveness measure that results the minimum waste of effort, time, and skill. Pour et al, (2019) discussed that one of the most crucial economic goals for countries, according to international organizations, is economic growth through efficiency. Hassan, et al, (2014) stated that a company with a high level of efficiency is often linked to better performance or profitability.…”
Section: Efficiencymentioning
confidence: 99%
“…For measuring hospital efficiency, we conducted a qualitative analysis, i.e., literature review and collecting opinions of experts to identify the input and output indicators. First, a scoping review of related studies identified a list of related indicators for the objectives of our research (17). Second, we examined the existence of data associated with each indicator and the reliability of the data source, according to which, many indicators were excluded.…”
Section: Data Collectionmentioning
confidence: 99%